2021
DOI: 10.3390/nu13103609
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteoprotegerin Is an Independent Marker of Metabolic Complications in Non-DialysisDependent Chronic Kidney Disease Patients

Abstract: Background: Osteoprotegerin (OPG) belongs to the tumour necrosis factor superfamily and is known to accelerate endothelial dysfunction and vascular calcification. OPG concentrations are elevated in patients with chronic kidney disease. The aim of this study was to investigate the association between OPG levels and frequent complications of chronic kidney disease (CKD) such as anaemia, protein energy wasting (PEW), inflammation, overhydration, hyperglycaemia and hypertension. Methods: One hundred non-dialysis-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Elevation of serum OPG level in the subjects with reduced eGFR has been previously reported [ 30 ]. Despite the debate on the role of circulating OPG in atherosclerotic disease [ 31 ], as an experimental study reported that exogenous OPG treatment lead to endothelial and vascular smooth cell dysfunction by promoting the production of reactive oxygen species, which may underlie vascular injurious effects in conditions such as hypertension [ 32 ], the phenotype of OPG-knockout mice ultimately indicates circulating OPG as a biomarker, rather than a mediator, of atherosclerosis, as OPG-deficient mice develop early onset arterial calcification [ 33 ].…”
Section: Discussionmentioning
confidence: 92%
“…Elevation of serum OPG level in the subjects with reduced eGFR has been previously reported [ 30 ]. Despite the debate on the role of circulating OPG in atherosclerotic disease [ 31 ], as an experimental study reported that exogenous OPG treatment lead to endothelial and vascular smooth cell dysfunction by promoting the production of reactive oxygen species, which may underlie vascular injurious effects in conditions such as hypertension [ 32 ], the phenotype of OPG-knockout mice ultimately indicates circulating OPG as a biomarker, rather than a mediator, of atherosclerosis, as OPG-deficient mice develop early onset arterial calcification [ 33 ].…”
Section: Discussionmentioning
confidence: 92%
“…As it was shown in the study of Rymarz et al, OPG was an independent marker which may identify patients with poor prognostic factors, e.g., overhydration in CKD [ 39 ]. Pericarditis is one of the complications of uremia.…”
Section: Discussionmentioning
confidence: 99%
“…OPG levels rise with kidney function decrease and the cause of its accumulation in uremic state remains unknown [ 44 ]. Rymarz showed that OPG is related with protein energy wasting (PEW), inflammation and metabolic disturbances in CKD patients [ 10 ]. Moreover, in the group of patients with CKD not treated with dialysis elevated OPG concentrations were associated with left ventricular hypertrophy, LVDD and the presence of pericardial fluid [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…eGFR was calculated according to the short Modification of Diet in Renal Disease (MDRD) formula [ 10 ]. GFR in mL/min per 1.73 m 2 = 175 × SerumCr − 1.154 × age − 0.203 × 1.212 (if patient is black) × 0.742 (if female).…”
Section: Methodsmentioning
confidence: 99%